1943
DOI: 10.1001/jama.1943.02840340013004
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Diabetes Mellitus in Rabbits With Alloxan

Abstract: have not to our knowledge been published. The solu¬ bility in buffers of acetylsulfathiazole, of which the urinary crystals are composed,30 increases only from 7 mg. per hundred cubic centimeters at pu 5.5 to 28 mg. per hundred cubic centimeters at pu 7.5, whereas the solubility of acetylsulfadiazine increases from 20 mg. per hundred cubic centimeters at pu 5.5 to 512 mg. per hundred cubic centimeters at pu 7.5. Two substituted sulfadiazine compounds, sulfamerizine and sulfamethazine, are at present receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1945
1945
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Thereafter, Brunschwig et al(1943) and Bailey and Bailey (1943) reported the inducement of a persistent diabetic state in animals. This milestone was soon followed by a wealth of studies and dis-…”
Section: Synopsismentioning
confidence: 99%
“…Thereafter, Brunschwig et al(1943) and Bailey and Bailey (1943) reported the inducement of a persistent diabetic state in animals. This milestone was soon followed by a wealth of studies and dis-…”
Section: Synopsismentioning
confidence: 99%
“…12 Although an orally active botanical substitute for insulin is unlikely, phytochemicals may stimulate insulin biosynthesis and promote insulin action. 13 Many plants with antidiabetic properties probably act in part through their content of fibre, vitamins or mineral content. To this end, plants rich in minerals have been shown to enhance glycaemic control in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…But when a special diet, consisting chiefly of wheat flour, was given to these reco vering animals, the reappearance of urinary sugar was confirmed. (Bailey et al, 1943Izeki, 1960. Also no difference was in the found average of the death rate for the 6-month period between the Tolb treated and untreated groups.…”
Section: Discussionmentioning
confidence: 81%